PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH (ICM) UNTUK MENINGKATAN KEAKTIFAN BELAJAR SISWA MATA PELAJARAN IPS TERPADU KELAS IX MTS NEGERI GEMOLONG - H. F., Siti Azhariyah (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
The teaching and learning process is important in learning effective and efficient learning outcomes with the activities of students who are actively involved in learning. This study aims to improve student learning activeness in the Integrated Social Sciences learning process and improve students' understanding through Index Card Match learning in Class IX MTS Gemolong State. The method used in the study is Class room Action Research, the implementation of which is carried out in two cycles. Data collection uses Observation. The results of the study at MTS Gemolong State showed that student activity increased pre cycle 61.56%. In the first cycle the speed became 70.22%, and the second cycle became 96.57%. Increased learning outcomes of students who have fulfilled the completeness value that is pre cycle is 8.33%. Then in the first cycle increases, which is to 72.22% and increases again in the second cycle to 75%.Keywords:Learning Activity, Learning Model, Learning Outcomes